Optimization of Digital Learning Media for Islamic Education: Increasing Students' Interest in Learning - Afifah Nur Hamidah; Hafidz (Fakultas Agama Islam Universitas Billfath, 2025)
This study aims to describe the optimization of digital learning media in Islamic Education to increase students' interest in learning at SMAN 3 Boyolali. Along with the development of technology, digital media has become an increasingly relevant strategy to create more interactive and engaging learning. The method used is descriptive qualitative research with data collection techniques through interviews, observations, and documentation. The study results show that using digital media such as Canva, Video, Google Classroom, Google Drive, Quizizz, and ClassPoint increases students' interest in learning based on four primary indicators: feelings of pleasure, interest, attention, and engagement. Canva and Video have proven more effective in increasing students' interest and understanding through attractive visual displays, while Quizizz and ClassPoint encourage active student engagement through gamification elements. Google Classroom and Google Drive function as a means of distributing materials and managing assignments, although they have limitations in terms of interactivity. Optimizing digital media in Islamic Education learning contributes to increasing interest in learning and encourages creating more dynamic learning to meet students' needs in the digital era. Therefore, teachers need to improve their skills in utilizing digital media through ongoing training. Schools are expected to strengthen their technological infrastructure, and further research using quantitative methods is required to measure the impact of digital media use on student learning outcomes in a more measurable manner.